Investigation of biofilm production and icaA and icaD genes in Staphylococcus aureus isolated from heifers and cows with mastitis - Castelani, Livia; Pilon, Lucas Eduardo [UNESP]; Martins, Thamires; Pozzi, Claudia Rodrigues; Arcaro, Juliana Rodrigues Pozzi (Wiley-Blackwell, 2015)
Biofilm formation and antimicrobial resistance of Staphylococcus aureus are important virulence factors in cases of mastitis in dairy cows. However, few studies have investigated mastitis strains isolated from heifers. Within this context, the objective of the present study was to investigate biofilm formation on Congo red agar, the presence of the icaA and icaD genes by polymerase chain reaction (PCR), and the percentage of in vitro antimicrobial resistance of 110 S.aureus isolates from mammary gland secretions of heifers and cows with mastitis. PCR detected the icaA and icaD genes in 98% and 100% of isolates, respectively. However, only 55.5% of all isolates produced a biofilm on Congo red agar. Antimicrobial susceptibility testing revealed that 47.0% of isolates from heifers and 70.4% of isolates from cows were resistant to at least one of the antimicrobial agents tested. Resistance to penicillin and/or ampicillin was the most frequent (44.5%). These results indicate the need to implement prophylactic and control measures of mastitis for heifers. Heifers and cows can carry resistant strains with the capacity of biofilm production, a fact representing a threat to public health and animal well-being and generating losses to dairy farmers.
Keywords: Congo red agar; Intramammary infection; PCR